Automation of green space maintenance along road infrastructure (Международный научный журнал «Инженер», 2026)
The study comprehensively examined the efficiency of automated irrigation systems applied to green areas along the Tashkent–Chirchik highway. Within the research framework, soil moisture sensors were utilized to continuously monitor environmental conditions and to optimize the allocation of water resources. This methodological approach enabled the collection of precise data on soil humidity levels, making it possible to design irrigation schedules that respond directly to the actual needs of the vegetation. The findings revealed a range of important outcomes. First, automation led to a reduction in water use by approximately 25–30%, which is a crucial achievement considering the growing problem of water scarcity in Central Asia. Second, labor requirements decreased by nearly 40%, thereby reducing the dependence on manual maintenance and significantly lowering operational costs. Third, plant resilience during the vegetation period was noticeably improved, as indicated by healthier leaf coloration, higher photosynthetic activity, and greater tolerance to drought stress.In addition, system management through IoT-based technologies allowed for real-time monitoring and rapid response to changing conditions, which significantly improved the speed and quality of maintenance services. This ensured more efficient allocation of limited resources, minimized the risks associated with over- or under-irrigation, and contributed to more stable plant growth. Overall, the adoption of automated irrigation and monitoring systems represents not only a technological advancement but also an important step toward achieving environmental sustainability, energy efficiency, and long-term landscape resilience. These results highlight the potential for wider application of such technologies along highways and in other urban green zones, where resource savings and ecological balance are of strategic importance.